GOVERNMENT TO EMPLOYES: PENERAPAN APLIKASI SISTEM INFORMASI LAYANAN ONLINE KEPEGAWAIAN (SiNOK) DALAM MENGUKUR KEDISIPLINAN APARATUR SIPIL NEGARA (ASN) DI PEMERINTAHAN KOTA TEGAL - Akhmad Habibullah; Dede Ferawati (Jurnal Agregasi, 2022)
In the government service system, there have been many significant changes in the digital era as it is today. Even in Indonesia, there are already many cities that implement e-government, one of which is the City of Tegal. The Tegal City Government implements e-government in the form of the SiNOK application which is used as a tool to make it easier for ASN in the Tegal City Government to carry out departure absences. The purpose of this study was to determine the effectiveness of using the SiNOK application in measuring ASN discipline in the Tegal City Government and to explain the inhibiting factors for the use of the SiNOK application when used by ASN in the Tegal City Government. This study uses a qualitative descriptive research method, with data analysis techniques using Nvivo analysis to obtain systematic analysis results. The results showed that the use of the SiNOK application was effective in increasing the discipline of ASN in the Tegal City Government, it could be proven that ASN was able to come and go home on time and was able to make good use of the time after the SiNOK application was implemented.